Effect of ranibizumab on retinopathy of prematurity: A meta-analysis - Wang, Zhibin; Zhang, Zhaobo; Wang, Yue; Di, Yu (Frontiers in Pharmacology, 2022)
The primary objective of this study was to systematically evaluate the clinical efficacy of intravitreal ranibizumab injection in the treatment for retinopathy of prematurity (ROP) in infants. The MEDLINE (PubMed), Embase, China Biology Medicine disc, Cochrane Library, Web of Science, WanFang Data, CNKI, and CQVIP databases were searched to collect randomized controlled trials (RCTs) comparing the efficacy of ranibizumab with laser treatment in ROP. The retrieval time was from 1966, on which the database was constructed until January 12, 2022. Data were extracted based on predetermined inclusion and exclusion criteria. Two investigators employed QUADAS-2 to independently assess the quality of all eligible original studies. Following quality evaluation, we also performed a meta-analysis using STATA v 15.1 and RevMan v 5.4 and funnel plots were used to detect publication bias. A total of five RCTs were included in the meta-analysis. According to the results, the retinal neovascularization rate of the intravitreal ranibizumab injection group was statistically higher than that of the laser therapy group [risk ratio (RR)=1.26, 95% confidence interval (CI): 1.18-1.35]; however, the incidence of adverse events, including recurrence and complications, was not different between them [RR=0.73, 95%CI: 0.19-2.80]. Therefore, intravitreal ranibizumab injection may be more clinically effective than laser therapy in the treatment for ROP. The safety and efficacy of ranibizumab in the long-term treatment for ROP needs further investigation.